CROSS-CULTURAL MARKETING RESEARCH: ADVANCING MEASUREMENT INVARIANCE PRACTICES FOR ROBUST EQUIVALENCE TESTING - Sistiana; Lukmanul Hakim; Dahrul Aman Harahap (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2026)
This study examines the current state of measurement invariance in cross-cultural marketing research, identifying a critical imbalance between widespread method usage and methodological rigor. Findings indicate that while Multi-Group Confirmatory Factor Analysis (MG-CFA) remains the dominant approach, its application is often incomplete, frequently stopping at configural or metric invariance. This failure to reach scalar invariance limits the validity of cross-cultural comparisons, particularly when comparing latent means. Furthermore, inconsistent reporting practices and a lack of transparency regarding model specifications and fit indices undermine the reproducibility and credibility of findings. The review identifies significant methodological challenges, including sample heterogeneity, cultural bias in measurement instruments, and limited statistical power, which complicate testing and lead to inconsistent results. Although advanced methodological trends like partial invariance and alignment optimization offer more flexible and nuanced solutions, their adoption remains uneven. This highlights a persistent gap between methodological innovation and actual research practices. To address these issues, the study recommends improving methodological training, standardizing reporting practices, and embracing open science to ensure more robust and reliable cross-cultural research.